SABERES DOCENTES DOS PROFESSORES QUE ATUAM NOS ANOS FINAIS DO ENSINO FUNDAMENTAL - COZZOLINO, Valeria de Andrade (2015)
The study seeks to know the developed work of teachers from different curricular components of the final years of Elementary Public Schools in the city of Sao Paulo in order to identify and understand their perceptions about the teaching knowledge in the context of teaching and learning process. So this study discusses the knowledge that teachers acquire and / or rework in the pedagogical practice and that they see as a changing possibility on the teaching and learning that includes a quality education. The adopted framework is guided in studies on teacher knowledge and practice, knowledge about the processes of teaching and learning and the training of teachers that work in the final years of Elementary School by using the main authors, Tardif, Garrido, Gatti and Luckesi. Therefore this study proceed to the analysis of official documents and the application of a questionnaire to twelve teachers from the final years of Elementary School in order to learn about aspects of professional life, as well as the joints they do between teaching knowledge, professional practices and teaching and learning process. The analyzes reveal that the contributions made by these authors are essential to guide the teaching in that to respect the mobilization / construction of knowledge necessary to teach from an educational praxis committed with knowledge, know-how and know-to be. Finally, the data show the need to ensure discussions about the curriculum of the courses of the final years of Elementary School in order to realize that the evolution that educators aspire to everyone involved in the teaching and learning is resignify in practice knowledge.